2008
DOI: 10.1590/s1415-47572008005000021
|View full text |Cite
|
Sign up to set email alerts
|

The historical biogeography of Pteroglossus aracaris (Aves, Piciformes, Ramphastidae) based on Bayesian analysis of mitochondrial DNA sequences

Abstract: Most Neotropical birds, including Pteroglossus aracaris, do not have an adequate fossil record to be used as time constraints in molecular dating. Hence, the evolutionary timeframe of the avian biota can only be inferred using alternative time constraints. We applied a Bayesian relaxed clock approach to propose an alternative interpretation for the historical biogeography of Pteroglossus based on mitochondrial DNA sequences, using different combinations of outgroups and time constraints obtained from outgroup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Ancestral populations isolated in these land blocks began to diverge from each other and eventually speciated. This hypothesis receives broad support for Amazonia (Aleixo, 2004; Aleixo & de Fátima Rossetti, 2007; Pereira & Wajnta, 2008). Several marine incursions occurred in the Congo Basin in the Mesozoic (Kimmeridgian, Cenomanian and Late Cretaceous), but from the Cenozoic the moderate uplift of the Cuvette borders made any possibility of a marine incursion remote (Giresse, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Ancestral populations isolated in these land blocks began to diverge from each other and eventually speciated. This hypothesis receives broad support for Amazonia (Aleixo, 2004; Aleixo & de Fátima Rossetti, 2007; Pereira & Wajnta, 2008). Several marine incursions occurred in the Congo Basin in the Mesozoic (Kimmeridgian, Cenomanian and Late Cretaceous), but from the Cenozoic the moderate uplift of the Cuvette borders made any possibility of a marine incursion remote (Giresse, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…The Saffron Toucanet ( Pteroglossus bailloni ), an endemic of the Atlantic Forest, was historically considered a monotypic genus ( Baillonius bailloni ) allied with Andigena due to the unique morphological characteristics of this species, notably its unique yellow plumage compared to the overall green coloration of other taxa in the genus Pteroglossus (Short and Kirwin 2020b). Several studies, which were based on mitochondrial or allozyme data, found that Baillonius was either sister to all other Pteroglossus (Hackett and Lehn 1997) or found within Pteroglossus (Barker and Lanyon 2000, Kimura et al 2004, Eberhard and Bermingham 2005, Periera and Wajntal 2008, and Patel et al 2011). Kimura et al (2004) argued that Baillonius bailloni should be subsumed into Pteroglossus .…”
Section: Discussionmentioning
confidence: 99%